c.2 - Gupta, S. P. (New Delhi, 2006)
A response to the 2002 report of the Indian government's planning commission, this well-researched and comprehensive discussion argues that India and other countries cannot sustain a high GDP growth and labor force with the present-day employment strategy, even with the help of government-subsidized programs. This contention, written by a leading authority in the field and a member of the Planning Commission, claims that the present development strategy will create more gaps between the "haves" and the "have-nots" and calls for a reexamination of the approach. The initial executive summary of the 2002 report is in the appendix for easy reference.
Keywords: Economic reforms